2015
DOI: 10.5585/gep.v6i1.305
|View full text |Cite
|
Sign up to set email alerts
|

Building Productivity in Virtual Project Teams

Abstract: The steady increase in project failure rates is leaving businesses searching for better integration techniques to virtualize their project environments. Through virtualization, organizations may have positive impacts on communities across geographical boundaries and resource constraints. The focus of this phenomenological study was to explore, via the experiences of successful project management practitioners, best practice strategies for integrating virtual project teams through data analysis. The conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Despite the increase in the number of virtual teams, studies show that virtual teams can aid in bringing about positive social change through a mentorship program in education by developing online learning forums or encouraging a paperless workplace (Hamersly & Land, 2015). Recent research has shown that beyond communication, sharing and generating knowledge has been important for virtual teams such as contributing to the software development by doing work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the increase in the number of virtual teams, studies show that virtual teams can aid in bringing about positive social change through a mentorship program in education by developing online learning forums or encouraging a paperless workplace (Hamersly & Land, 2015). Recent research has shown that beyond communication, sharing and generating knowledge has been important for virtual teams such as contributing to the software development by doing work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The identification of relevant strategies leads to a structure that accommodates skills and technology, governance, and collaborative practices in different environments (Hamersly & Land, 2015). Competitive manufacturing, which delights customers, requires not only the development of WCM but also the continuous evolution and improvement of processes (Peças et al, 2021;Arms et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a way of thinking as to how to act in a diverse environment, simultaneously covering essential project management components, such as resources, timing etc. (Hamersly & Land, 2015). A study by Saafein & Shaykhian (2014) shows the influence of unity and collaboration on the performance of virtual teams.…”
Section: Collaboration In Multicultural Teammentioning
confidence: 99%